Physicochemical and Sensory Evaluation of Ripe Banana Jam Products - Nurul Amirah Mohamad Diah; Saliza Asman (Enhanced Knowledge in Sciences and Technology, 2024)
Bananas are one of the most extensively consumed fruits in the world due to their unique taste, dietary value, and versatility. The main ingredient in the production of banana jams is banana, sugar, and pectin. The objective of this study is to evaluate sensory characteristics of ripe banana jam from Musa acuminata and Musa paradisiaca as well as to examine the physicochemical properties of ripe banana jam from Musa acuminata and Musa paradisiaca. Physicochemical analysis that was carried out in this study are colour analysis, total soluble solids analysis, ash percentage analysis, pH analysis, moisture analysis, viscosity analysis, and texture analysis. From the results, total soluble solids were found to be in the range between 60 to 66% Brix, with ash content of 2.31% for M. acuminata and 1.06% for M. paradisiaca, pH value ranges between 3.5 to 4.2. The moisture content means for both samples, M. acuminata and M. paradisiaca are 33.8 and 27.95, respectively, with findings of texture reading that include hardness at range of 58.0 to 67.0 and stickiness at range of -40 to -50. It is summarised from the results of the physicochemical study and sensory evaluation that Musa acuminata jam has been found to be more preferable compared to Musa paradisiaca jam.